2008
DOI: 10.1111/j.1439-0272.2008.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in semen parameters of toll collectors working at motorways: does diesel exposure induce detrimental effects on semen?

Abstract: Air pollution is contemporarily considered to be a significant cause in impairing semen parameters. The aim of this study was to investigate possible effects of traffic pollutants, mainly the diesel exposure, on semen analysis. A total of 38 men working as toll collectors at motorways formed the study group. Simultaneously, 35 men working as office personnel constituted the control group. Factors including varicocele, chronic diseases that can affect sperm production were the exclusion criteria. No difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 37 publications
(36 reference statements)
1
36
0
1
Order By: Relevance
“…One possible reason for this alteration appears to be exposure to toxic substances in the environment, and notably ambient air pollution [54][55][56]. It has indeed been demonstrated that professions exposed to exhaust, such as toll collectors working on expressways, more frequently develop sperm abnormalities [16,57].…”
Section: Impact Of Air Pollution On the Male Gametementioning
confidence: 99%
See 3 more Smart Citations
“…One possible reason for this alteration appears to be exposure to toxic substances in the environment, and notably ambient air pollution [54][55][56]. It has indeed been demonstrated that professions exposed to exhaust, such as toll collectors working on expressways, more frequently develop sperm abnormalities [16,57].…”
Section: Impact Of Air Pollution On the Male Gametementioning
confidence: 99%
“…These alterations involves a reduction in sperm mobility [54,[56][57][58][59][60][61][62], or in the quality of their movement [54,56]. Altered sperm morphology with a reduction in the percentage of normal shapes, notably the morphology of the head, is also frequently mentioned [21,56,57,[59][60][61][62][63][64][65][66].…”
Section: Impact Of Air Pollution On the Male Gametementioning
confidence: 99%
See 2 more Smart Citations
“…Findings include abnormal sperm count, mobility and morphology (Guven et al, 2008) and a significantly higher percentage of spermatozoa with damaged chromatin and DNA fragmentation (Calogero et al, 2011) in toll-gate workers. In male traffic policemen, lower free testosterone (Sancini et al, 2011) and higher luteinizing hormone (Tomao et al, 2009) and follicle-stimulating hormone (Tomei et al, 2009) plasma levels were reported.…”
Section: Rationalementioning
confidence: 99%